Quantification of rock mass disturbance using rock-mass property, rock characterization and blast characterization in underground hard-rock - Sharifzadeh, Mostafa; Pal, M. (2014)
The rock-mass disturbance due to engineering activities is an important factor to estimate strength and deformability of rock-mass. Blasting practice in underground hard-rock mining is very common and so as disturbance generated due to blast. Degree of disturbance due to blasting varies with different rock type, rock characteristics and properties and blast characteristics. To estimate the most realistic strength and deformability of rock-mass in underground hard-rock it is necessary to estimate the extent of disturbance. However quantification of disturbance factor has been done already using factors such as geological strength index and uniaxial compressive strength of rock-mass which gives value of disturbance factor as 0 for good blast and 1 for poor blast. Previous quantification approach provides general values of disturbance factor "D" with limited factor however approach gives very strong and clear background for further research. Also previous research helps in providing comprehensive information about the disturbance in rock-mass. This paper includes numerical and empirical estimations using real-time data from underground hard-rock mine and hence provides a new relationship to quantify the value of disturbance factor "D". In this paper rock-mass characterization, rock properties and blast characterization are taken into account. Elemental analysis has been done on major factors associated with rock-mass characterization, rock properties and blast characteristics which affect disturbances in rock-mass due to blasting. Accordingly rock-mass characterization influences blast 54% whereas rock properties and blast characterization influence 28% and 18%. Result shows that rock-mass with different characteristics and properties behave differently with blast characterization and hence the degree of disturbance generated due to blasting changes accordingly.